Electrical and Thermal and Self-Healing Properties of Graphene-Thermopolyurethane Flexible Conductive Films - Ke Wang; Zhimin Zhou; Jiahao Zhang; Jinyuan Tang; Peiyu Wu; Yuehui Wang; Yuzhen Zhao; Yong Leng (Nanomaterials, 2020)
We fabricated graphene-thermopolyurethane (G-TPU) flexible conductive film by a blending method and systematically investigated the electrical, thermal and self-healing properties of the G-TPU flexible conductive film by infrared light and electricity. The experimental results demonstrate that the G-TPU composite films have good conductivity and thermal conductivity in the appropriate mass content of graphene in the composite film. The composite films have the good electro-thermal and infrared light thermal response performances and electro-thermal response performance is closely related to the mass content of graphene in the composite film, but the infrared light thermal response performance is not. The scratch on the composite film can be completely healed, using electricity or infrared light. The healing efficiency of the composite film healed using infrared light is higher than that of using the electricity, while the healing time of the composite film is shorter. Regardless of the self-healing method, the temperature of the self-healing is a very important factor. The self-healing conductive composite film still exhibits a good conductivity.